The Impact of Reich’s Vegetotherapy on Emotional Regulation and Postural Balance in Military Personnel: A Non-Pharmacological Approach to Combat Stress - Sana Khadhrani; Imed Touhemi; Amri Hammami; Chiraz Goumni; Jihen Khalfoun; Mohanad Omar; Rebai Haithem; Abderraouf Ben Abderrahman (American Journal of Men's Health)
Military operations subject soldiers to intense stress, which can adversely affect both their emotional regulation and physical balance. This study examines the effectiveness of Reich’s vegetotherapy (VGT), an alternative non-pharmacological intervention, in improving these critical areas among military personnel. A total of 29 soldiers, with an average age of 30, were randomly assigned to either an experimental group (EG; 15 soldiers) or a control group (CG; 14 soldiers). Over a period of 6 weeks, the EG participated in twice-weekly VGT sessions, while the CG received no intervention. The intervention group showed a significant reduction in anxiety levels, with scores improving from the beginning to the end of the test ( p  = .001) and a significant time × group interaction ( p  = .003). The EG experienced a greater improvement (-68%) compared to the CG (−9%) ( p  = .036). In the open-eyes postural balance test, the EG showed a significant improvement ( p  = .029), with a time × group interaction effect ( p  = .04), although no significant difference was found between the groups ( p  > .05). The EG improved more (−36%) compared to the CG (24%). In addition, anger levels significantly improved post-intervention ( p  = .001), with a significant time × group interaction ( p  = .001). These findings suggest that Reich’s VGT may serve as an effective method for mitigating stress-related impairments in military personnel. Further research with larger sample sizes is necessary to validate these results and explore its broader applications.